THE EFFECT OF HEALTH EDUCATION ON FAMILY'S ABILITY LEVEL IN GANGRENE WOUND CARE AT DIABETES MELLITUS PATIENTS IN TURI COMMUNITY HEALTH CENTERS, LAMONGAN - Umam, Khotibul; Habibah, Mita Nur; Lutfiandini, Cherlys Tin; Medawati, Riris (Journal of Vocational Nursing, 2022)
Introduction: Diabetes Mellitus causes neuropathy and abnormalities in blood vessels that cause changes in the skin and muscles, making it easier for gangrene to occur. Gangrene wounds that are left untreated or treated inappropriately can spread and increase the risk of amputation and death. Proper gangrene wound care is needed to speed up the healing process and prevent the wound from getting worse. Diabetes mellitus patients with wound gangrene need the help of other people (family) to carry out independent care at home. So that, the ability of the family to carry out proper care is needed. Methods: The design in this study used an analytical pre-experimental design with a one-group pre-test and post-test approach. The sampling of this study was total sampling used the Paired Sample T-Test. The population in this study was family who caring for family members with gangrene wounds at the Turi Community Health Center which met the inclusion criteria namely 25 respondents. Results: The results of this study showed that T = -3.361 means that there is an influence between the level of family ability in gangrene wound care before and after being given Health Education about Gangrene Wound Treatment. Conclusions: Health Education has a significant effect on the Family's Ability Level in gangrene wound care.